2022
DOI: 10.1002/nbm.4818
|View full text |Cite
|
Sign up to set email alerts
|

Low‐cost inductively coupled stacked wireless RF coil for MRI at 3 T

Abstract: Inductively coupled RF coils are an inexpensive and simple method to realize wireless RF coils in MRI. They are low cost and can greatly ease the MR scan setup and improve patient comfort, since they do not require bulky components such as cables, baluns, preamplifiers, and connectors. Previous works have typically used single-layer loops as wireless coils. In this work, we present a novel wireless coil, where two loops are stacked and decoupled with a shared capacitor. We found that such a stacked structure c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…An alternative way to realize the wireless coil with a much lower cost and simpler design is through inductive coupling technology, 9–18 as illustrated in Figure 1. The inductively coupled coil can be traced back to the early days of MRI 19–21 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…An alternative way to realize the wireless coil with a much lower cost and simpler design is through inductive coupling technology, 9–18 as illustrated in Figure 1. The inductively coupled coil can be traced back to the early days of MRI 19–21 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has demonstrated that wireless loop coils can be detuned using a passive detuning circuit 10,17,30 . However, detuning volume‐type wireless coils is much more challenging because of their complex structure and multiple resonant modes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations